Genetic parameters of soybean populations obtained from crosses between grain and food genotypes - Giaretta Azevedo, Cleber Vinicius [UNESP]; Pedroso Val, Bruno Henrique [UNESP]; Andrade de Araujo, Lilian Cristina [UNESP]; Pinto Juhasz, Ana Cristina; Di Mauro, Antonio Orlando [UNESP]; Uneda-Trevisoli, Sandra Helena [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2021)
In addition to the agronomic traits of interest, soybean cultivars destined for human consumption must have specific attributes that meet the demands of the consumer market. To meet this demand, this study aimed to select progenies with agronomic and commercial traits of interest from soybean populations obtained from crosses between different food and grain genotypes and to estimate the genetic parameters of these populations. The F-3:4 and F-4:5 progenies that originated from the two crosses were evaluated in the 2015/16 and 2016/17 agricultural years, respectively, using the pedigree method. The experimental design utilized augmented blocks, while statistical analyses were performed by using the REML/BLUP methodology. The evaluated traits were plant height at maturity (APM), insertion height of first pod (AIV), lodging (AC), agronomic value (VA), number of pods per plant (NV), number of days to maturity (NDM), number of branches (NR), number of nodes (NN), 100-seed weight (PCS), and grain yield per plant (PG). The best progenies were selected, and the following genetic parameters were estimated: genetic variance, phenotypic variance, heritability, and selective accuracy. The estimates of the genetic parameters indicate the presence of high genetic variance in these populations. Heritability was high for most of the traits, indicating good potential for the selection of superior genotypes.
Keywords: Glycine max; pedigree method; REML/BLUP; variance components